Efficacy and safety of switching to raltegravir plus atazanavir dual therapy in pretreated HIV-1-infected patients over 144 weeks: a cohort study. (December 2014) - Gantner, Pierre; Koeppel, Christine; Partisani, Marialuisa; Batard, Marie-Laure; Bernard-Henry, Claudine; Cheneau, Christine; De Mautort, Erik; Priester, Michele; Muret, Patrice; Sueur, Charlotte; Fafi-Kremer, Samira; Rey, David
Abstract Background: To decrease drug burden among HIV-1-positive adults, we need a new gold standard for antiretroviral therapy maintenance strategies. Methods: This retrospective study aimed to assess efficacy in maintenance strategy of atazanavir (ATV) and raltegravir (RAL) dual therapy. The proportion of patients with HIV-1 RNA < 40 copies/ml at specific time points was recorded. Immunological response, safety, and pharmacokinetics were assessed. Results: Overall, 39 patients were switched to a RAL/ATV (n = 32) or RAL/ATV plus ritonavir (n = 7) regimen. Almost all patients (95%) received RAL twice daily. Most patients (70%) received a 400 mg ATV dosing per day, once (26%) or twice daily (44%). The percentages of virological success at weeks 24, 48, 96, and 144 were 92% (95% confidence interval (CI), 83–10), 86% (95% CI, 74–98), 70% (95% CI, 52–88), and 63% (95% CI, 42–84), respectively. Overall, 12 (31%) patients stopped dual therapy: 7 patients because of adverse events, mostly clinical myositis (n = 3). Confirmed virological failure occurred in three patients; two of them developed RAL resistance patterns. A significant increase in the CD4+/CD8 + T-cell ratio was observed at week 48 (p < 0.005). Only grade 1–2 adverse events were observed. Trough plasma levels presented a wide variability. Suggested trough concentrations were achieved in 79% and 94% of patients for ATV and RAL, respectively. An unboosted 400 mg per day ATV dosing seemed to be appropriate, regarding the targeted levels achieved and the lack of grade 3 or 4 hyperbilirubinemia. Conclusions: We demonstrated, on a 3-year follow-up, the efficacy and safety of RAL plus ATV maintenance dual therapy.